EFL TEACHERS’ PERCEPTIONS AND INSTITUTIONAL MANAGEMENT PRACTICE OF PROFESSIONAL DEVELOPMENT IN SELECTED ETHIOPIAN UNIVERSITIES - Mekie, Mulualem Eshete (LLT Journal: A Journal on Language and Language Teaching, 2021)
This paper intended to assess EFL Teachers’ Perceptions and Institutional Management Practice of Professional Development in Ethiopian Universities. This research utilized a qualitative research design. Furthermore, the researcher used purposeful sampling, therefore, applied a semi-interview to the participants and was purposively selected to see how the participants were verbalized their perceptions and experiences of professional development. As a method of data analysis thematic analysis process included transcribing, translating, reading, coding, themes construction, and analysis. The findings indicated first; participants have a diverse understanding of professional development. Second, EFL teachers have a good perception of professional development. Third, teachers didn’t have direct participation in program designing processes individually and institutional level. Fourth, participants have a common understanding of the characteristics of an effective professional development program. Additionally, participants have a common understanding of the focus area of the ELT professional development program. This study recommended that the government and stakeholders consider the problem on the ground and the program should be content-specific. The management practices of professional development have to be assessed, followed, and supervised by the responsible organs which are assigned to facilitate and control the implementation. Finally, the program needs to be on the needs assessment, and important gaps should be identified.